2017
DOI: 10.1007/s10096-016-2895-2
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter baumannii bacteraemia in patients with haematological malignancy: a multicentre retrospective study from the Infection Working Party of Jiangsu Society of Hematology

Abstract: Acinetobacter baumannii (Ab) bacteraemia in patients with haematological malignancies is fatal but rarely reported. We explored the clinical characteristics, drug resistances and prognostic factors in these patients. This multicentre, retrospective study was conducted at the department of haematology wards of 18 tertiary hospitals in China from January 2014 to June 2015. The total clinical isolates from every source were collected from patients with haematological malignancy. Haematological malignancy patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 32 publications
2
18
0
3
Order By: Relevance
“…В проведенном нами исследовании нечувствитель ность к карбапенемам была выявлена у 74,3% изолятов A. baumannii. По результатам ряда других исследова ний, посвященных изучению A. baumannii, выделенных из гемокультуры больных гемобластозами, доля кар бапенемонечувствительных изолятов варьировала от 36,1% [5] до 100% [6]. О различиях в уровне устой чивости к карбапенемам сообщалось и среди изолятов A. baumannii, выделенных в многопрофильных стацио нарах.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…В проведенном нами исследовании нечувствитель ность к карбапенемам была выявлена у 74,3% изолятов A. baumannii. По результатам ряда других исследова ний, посвященных изучению A. baumannii, выделенных из гемокультуры больных гемобластозами, доля кар бапенемонечувствительных изолятов варьировала от 36,1% [5] до 100% [6]. О различиях в уровне устой чивости к карбапенемам сообщалось и среди изолятов A. baumannii, выделенных в многопрофильных стацио нарах.…”
Section: Discussionunclassified
“…Согласно результатам ряда исследо ваний, в России доля A. baumannii, выделенных из гемо культуры больных опухолями системы крови, составляет 3-4% [2][3][4]. По данным литературы, этот показатель ва рьируется от 2,9% до 6% [5,6], а у реципиентов гемо поэтических стволовых клеток достигает 11,8% [7]. По результатам российского многоцентрового эпидемио логического исследования антибиотикорезистентности возбудителей нозокомиальных инфекций «МАРАФОН», проведенного в 2013-2014 гг., в многопрофильных ста ционарах доля A. baumannii составила 13,7% от всех вы деленных бактериальных изолятов [8].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…It is well known that ICU is a very common place to contract an infection, especially from A. baumannii, which mainly includes the following two reasons. As regard patient's factors: long hospital stay [5], experience of invasive procedures (CVC [35], surgery [1,36], mechanical ventilation [37]), exposure to antibiotics [1,36] such as carbapenems, weak immunity (previous hormone therapy [36], tumor patients with neutropenia [38]). As regard the contamination of wards [39] A. baumannii is a bacterium commonly present in ICU that is difficult to eliminate and it often spreads among the ward crowd, resulting in a high risk of A. baumannii colonization for patients [40,41].…”
Section: Mdr-a Baumannii Bsismentioning
confidence: 99%
“…Overall, previous studies found that the prognosis of A. baumannii BSI in ICU patients is different depending on the underlying disease, illness severity, drug resistance, therapies used, post-infection appearance and infection source. The following characteristics often lead to poor prognosis: improper initial antibiotic treatment [9,38], comorbidities (tumours [38,44,45], liver cirrhosis [46], chronic obstructive pulmonary disease and chronic renal failure [37]), high drug resistance, neutropenia [38], previous high-dose hormone therapy [47], previous surgery [9], infection originated from the respiratory tract [35,46], high SAPS score [8], Pitt score [35], APACHE II score [37,38,46]. However, the development of septic shock [47] and the severity of the disease are the factors most closely related to prognosis, and our study also found these two key points.…”
Section: Prognostic Analysis Of Mdr-a Baumannii Bsismentioning
confidence: 99%